Analysis Of Football Players' Practical Application Of Tactical Attacking Methods (Journal of Pedagogical Inventions and Practices, 2025)
This article examines various aspects of attacking actions by football players during competitions among players aged 16-17. It highlights the balance between attacks conducted through the center and flanks, as well as instances of shots during critical moments. Additionally, the study discusses combinations involving players during attacking actions